Analisis Faktor – Faktor yang Memengaruhi Kinerja Keuangan pada Pusat Pendapatan Pemerintah Daerah Kabupaten Tulang Bawang - Hafizh Billy Anisman (Reviu Akuntansi, Manajemen, dan Bisnis, 2021)
AbstractPurpose: The purpose of this study is to determine the factors that affect the financial performance of government revenue centers.Research Methodology: Qualitative descriptive method is the method used in this research. The factors that influence the financial performance of the Regional Agency of Tulang Bawang Regency increasing the realization of Regional Revenue are described in this study, in order to identify the causes of the unrealized local revenue. Results: Judging from the efficiency factor, it shows that financial performance is classified as very efficient and after analyzing various factors, a strategy is sought that can be used by the Regional Revenue Service of Tulang Bawang Regency to provide an increase in the level of regional basic income which is the purpose of this study.Limitations: The implementation of the research will definitely be faced with its limitations, both in the results of the research discussion and the questionnaire questions in the research. This research cannot explain further about Regional Levies because in this case, the Regional Revenue Agency is only the coordinator of Regional Original Revenue.Contribution: In the future, this research is also expected to be a reference for the Regional Revenue Agency of Tulang Bawang Regency in order to increase the realization of the initial income of Tulang Bawang Regency.